P195 Effect of a reduced follow-up schedule on patient satisfaction with care among early-stage endometrial cancer patients: one-year preliminary results of the ENSURE randomized controlled trial. (1st November 2019) - Ezendam, NPM; de Rooij, BH; Creutzberg, CL; Kruitwagen, RFPM; van Lonkhuijzen, LR; Apperloo, MJA; Gerestein, K; Baalbergen, A; Boll, D; Vos, MC; van de Poll-Franse, LV
Abstract : Introduction/Background: It has been hypothesized that the frequency of follow-up visits for patients with early-stage endometrial cancer could be decreased. Therefore, the aim of the ENSURE trial was to assess patient satisfaction at 3-years follow-up among patients receiving a reduced follow-up schedule (4 visits/3 years) compared to patients receiving follow-up care according to Dutch guideline (10–13 visits/5 years). In the current analysis 1-year results were evaluated. Methodology: In this Dutch multicenter non-inferiority trial 320 patients diagnosed with stage 1A/B low-risk endometrial cancer, for whom adjuvant radiotherapy is not indicated, were randomized. Patients allocated to the reduced-follow-up group (n=162) and to the control group (n=158) were asked to complete questionnaires at baseline, after 6 and 12 months. Primary outcome was patient satisfaction with follow-up care as assessed with the Patient Satisfaction Questionnaire III (total scale) at 3-year follow-up. The predefined non-inferiority margin was 6 points (maximum acceptable difference), with a range of 0 to 100. Mixed linear regression and intention-to-treat analyses were used. Results: At 1-year follow-up, 272 participants had completed the questionnaire (85%). Preliminary results showed that the average satisfaction with care (total scale) score was 83 (SD=13) in the reduced follow-up arm and 82 (SD=13) in the control arm, where a higher score denotes a higher satisfaction (p=0.96). Also, technical competence of the health care provider and interpersonal aspects were scored equally in both groups, 81 (SD=15; p=0.52) and 87 (SD=14; p=0.95), respectively. Finally, access to care was evaluated similarly by patients in the reduced follow-up arm (M=81; SD=15) and the control arm (M=78; SD=15), p=0.39. Conclusion: These findings indicate no difference in satisfaction with care after 1-year follow-up among early stage endometrial cancer patients who receive a reduced follow-up schedule compared to patients receiving follow-up according to the Dutch guidelines. For final conclusions 3-year results of this trial need to be awaited. Disclosure: The study was funded by the Dutch Cancer Society (IKZ 2014-6677). The authors report no disclosures. Trial registration: NCT02413606 .